ANALISIS DAN PERANCANGAN SISTEM ELECTRONIC MEDICAL RECORD (EMR) BERBASIS WEB PADA KLINIK MATA KAMBANG - Marthiawati, Noneng; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2017)
Electronic Medical Record (EMR) is a medical record system that uses electronics based on a sheet ofpaper / medical record file in the handling of patients. However, this EMR system does not alwaysdevelop rapidly in other Hospitals / Clinics / Health Care Centers, one of them at Kambang Eye Clinic.The purpose of analyzing data processing on the business process of medical record in Kambang EyeClinic which there are still many obstacles such as lack of data accuracy, frequent inconsistency andredundancy of data, and the length of process of searching and accessing data needed because there is nointegrated system between one with other. As well as designing Electronic Medical Record System (EMR)Web Based on Kambang Eye Clinic is using PHP programming language and using object-basedmodeling techniques to describe the analysis and system design, namely in the form of use case diagrams,class diagrams, and activity diagrams. The output of this research is the design of prototype systemAnalysis and Design of Electronic Medical Record System (EMR) Based on Kambang Eye Clinic